On the limiting behavior of a harmonic oscillator with random external disturbance. (1995) - Kulinich, G. L.
Abstract : This paper deals with the limiting behavior of a harmonic oscillator under the external random disturbance that is a process of the white noise type. Influence of noises is investigated in resonance and non-resonance cases.